Typical Mental Disorders among Teens - Imran Karim, Muhammed Kashif Shaikh, Syed Zulfiquar Ali Shah, Ishrat Bibi, Noor Ul Ain Maham Bibi, Iqra, Sabiha Arain, (Pakistan Journal of Medical & Health Sciences, 2023)
In the past 20 to 30 years, adolescent rates of psychological illnesses and mental health issues appear to have risen significantly. The increase is a result of societal change, such as the disintegration of family structure, the increase in youth unemployment, and the intensification of educational and occupational pressures.1 The estimated incidence of psychological disorders among 11 to 15-year-olds in the United Kingdom is 11%, with disruptive behaviors being more prevalent in males and anxiety and depression being more prevalent in girls while among school going children of Pakistan it is reported as 10-20%2,3. As a result of adolescent instability, educators and parents may dismiss difficulties. Due to their developmental desires to be "normal" at a period when they're addressing mental problems and trying to communicate with a peer group, adolescents are frequently hesitant to seek treatment4.